Endoscopic Ultrasonography in the Diagnosis of Gastric Subepithelial Lesions - Eun Jeong Gong; Do Hoon Kim (Korean Society of Gastrointestinal Endoscopy, 2016)
Subepithelial lesions occasionally found in the stomach of patients undergoing endoscopy may be either benign lesions or tumors with malignant potential. They may also appear due to extrinsic compression. Discrimination of gastric subepithelial lesions begins with meticulous endoscopic examination for size, shape, color, mobility, consistency, and appearance of the overlying mucosa. Accurate diagnosis can be achieved with endoscopic ultrasonography, which provides useful information on the exact size, layer-of-origin, and characteristic morphologic features to support a definitive diagnosis. Endoscopic ultrasonography also aids in the prediction of malignant potential, especially in gastrointestinal stromal tumors. Features of subepithelial lesions identified on endoscopic ultrasonography can be used to determine whether further diagnostic procedures such as endoscopic resection, fine needle aspiration, or core biopsy are required. Endoscopic ultrasonography is a valuable tool for diagnosis and clinical decision making during follow-up of gastric subepithelial lesions.